The Effect of Extensive Interval Training Methods and Fartlek Training Methods on Increasing Cardiovascular Endurance in Football Athletes - Hesya Fauzi Alfarisi; Alen Rismayadi; Mona Fiametta Febrianty (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of extensive interval training and fartlek training methods on improving the cardiovascular endurance of soccer athletes. Cardiovascular endurance, as measured by VO2max, is a fundamental physical component in soccer because it determines an athlete’s ability to maintain optimal performance throughout a 2 x 45-minute match. Good endurance allows players to perform repeated high-intensity activities, such as sprinting, pressing, and rapid changes of direction, while maintaining concentration until the end of the match. This study used an experimental method with a two-group pretest-posttest design. The study sample consisted of 22 U-16 soccer athletes who were divided ordinally into two groups: an extensive interval training group and a fartlek training group, each consisting of 11 athletes. The test instrument used to measure cardiovascular endurance was the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1). Data analysis was carried out through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests to determine differences in effects between groups.